Pengaruh Pemahaman Standar Akuntansi Pemerintah, Pemanfaatan Sistem Informasi Akuntansi Dan Sistem Pengendalian Internal Terhadap Kualitas Laporan Keuangan Pada BPKAD Provinsi Jawa Tengah - Yunitasari, Febby Ana; Setyowati, Lilis; Durya , Ngurah Pandji Mertha Agung; Pamungkas, Imang Dapit (LPPM POLITEKNIK LP3I BANDUNG, 2024)
The purpose of this study is to determine how the quality of financial reporting in the Regional Financial and Asset Management Agency of Central Java Province (BPKAD) is affected by understanding accounting standards, using accounting information systems, and internal control systems. The research employed a quantitative methodology utilizing primary data. by means of a questionnaire survey that involved 58 of all 125 BPKAD employees in Central Java Province. Methods for data analysis, such as validity, reliability, classical acceptance testing, and multiple linear regression, were implemented using the program SPSS 24. The study's findings indicate that internal control systems, accounting knowledge, and the usage of accounting information systems all partially and simultaneously affect the quality of financial reporting, accounting for 57.9% of the sample. The remaining 42.1% is impacted by variables not taken into account in the study